Synthesis of Magnetic Base Catalyst from Industrial Waste for Transesterification of Palm Oil - Krishnan S.G.; Pua F.-L.; Lim H.-H. (Diponegoro University, 2023)
Biodiesel; C (programming language); Carbon dioxide; Catalyst activity; Lime; Scanning electron microscopy; Temperature programmed desorption; Transesterification; Base catalyst; Biodiesel production; Carbide lime; Carbide lime waste; Impregnation methods; Large amounts; Magnetic catalysts; Synthesised; Transesterifications; ]+ catalyst; Magnetism